Influence of artocarpus altilis fruit extract on cancer cell - Ganeson, Suhassni; Abdul Jamil, Muhammad Mahadi; Ambar, Radzi; Abdul Wahab, Ridhwan (Institute of Electrical and Electronics Engineers Inc., 2019)
Conventional chemopreventive agents causes adverse side effects in cancer patients. Thus, this study focuses on the effects of natural plant extract against cancer cell as a way to reduce or detrimental effects of orthodox drugs. The present study emphasizes on anti-cancer potentiality of Artocarpus altilis fruit extract against cervical cancer cell. Cervical cancer cell treated with methanol extract of artocarpus altilis fruit with the concentration varied from 10μg/ml, 20μg/ml, 30μg/ml, 40μg/ml and 50μg/ml. Treated and untreated (cells without treatment) cell proliferation and half maximal inhibitory concentration IC50 measured after 72 hours of incubation. Cells without treatment, 10μg/ml, 20μg/ml, 30μg/ml, 40μg/ml and 50 μg/ml of extract concentration showed 1.3, 0.98, 0.72, 0.65, 0.51, and 0.3 of cell proliferation factor accordingly with 40μg/ml of IC50 value. The result shows that artocarpus altilis is capable in opposing cervical cancer cell proliferation or growth as the proliferation factor decreases with the increasing dose of extract concentration which can be attributed to the presence of bioactive compound in Artocarpus altilis.